Inconstitucionalidade do § 3º do art. 792 do Código de Processo Civil por violação à segurança jurídica - Rivitti, Maria Augusta da Matta (2017)
The scope of this research is to analyze section 792, 3rd paragraph of the Brazilian Code of Civil Procedures, as it deals with the starting point of frauds in execution actions in cases of disregard of legal entities. The disregard of legal entity regulated by substantial law in several dispositions and fraud to execution actions regulated by procedural law were addressed by the Brazilian Code of Civil Procedures (Federal Law no. 13,097 of March 16th, 2015) in an innovative manner. This study enters the most relevant aspects of both doctrines (disregard of legal entity and fraud to execution actions), undertakes the exam of the case law concerning the starting point of fraud to execution actions, and then proceeds to analyze if the solution proposed by the new law insures legal certainty, core subject of the instant research. The study of this matter is justified by the dissent found in scholarly works and in case law and also by the direct impact over business transactions. The deductive method was applied, by means of bibliographical and case law research on the abovementioned doctrines. It was ascertained that the disposition under exam violates legal certainty, leading to its unconstitutionality